Quantitative proteomics analysis based on tandem mass tag labeling coupled with labeling coupled with liquid chromatography-tandem mass spectrometry discovers the effect of silibinin on non-alcoholic fatty liver disease in mice. Issue 3 (1st March 2022) - Wang, Yichao; Zhao, Hang; Yang, Liying; Zhang, He; Yu, Xian; Fei, Wenjie; Zhen, Yunfeng; Gao, Zhe; Chen, Shuchun; Ren, Luping
ABSTRACT: In recent years, the beneficial effects of silibinin (SIL) on nonalcoholic fatty liver disease (NAFLD) have attracted widespread attention. We tried to study the intervention effect of SIL on NAFLD, and explore the potential mechanisms and targets of SIL on NAFLD improvement. Thirty-three male C57BL6/J mice were divided into three groups, and, respectively, fed a normal diet (ND), a high-fat diet (HFD) or a HFD given SIL treatment (HFD+SIL). Biochemical indexes and histopathological changes of mice in each group were detected. In addition, quantitative proteomics analysis based on tandem mass tag (TMT) labeling coupled with liquid chromatography-tandem mass spectrometry (LC-MS/MS) and bioinformatics analysis was performed on protein changes in the livers. SIL could reduce the weight of mice, reduce liver lipid deposition, and improve glucose metabolism. Through comparison among the three experimental groups, a total of 30 overlapping proteins were found. These identified proteins were closely linked to liver lipid metabolism and energy homeostasis. Moreover, some drug targets were found, namely perilipin-2, phosphatidate phosphatase LPIN1, farnesyl pyrophosphate synthase, and glutathione S-transferase A1. In conclusions, high-fat diet increases the expressions of proteins implicated in lipid synthesis and transport in the liver, which can result in disorders of liver lipid metabolism. SIL can decrease liver lipid deposition and increase insulin sensitivity by regulating the expressions of these proteins. It not only improves the disorder of lipid metabolism in vivo, but also improves the disorder of glucose metabolism. Graphical Abstract: uf0001